1 - The Shifting Landscape of Development Cooperation: Repercussions for African Higher Education - Damtew Teferra, (Journal of Higher Education in Africa, 2014)
The higher education system in Africa is typically an amalgam of European and American higher education models. The system was built through the conception, direct intervention and support of the colonialists before other important players, such as private foundations, joined in. By design, African higher education was expected to become part of the global higher education system – albeit marginally – and without the consent of Africans. Nevertheless, the dynamics of development cooperation has been evolving with the emergence of new global players, the diminishing influence of the North, and sustained economic growth in Africa. This article (i) explores prospects and challenges based on recent developments and past experience; (ii) analyses current and emerging global trends; and (iii) concludes, with views, on what Africa ought to be doing by way of higher education partnerships.